2018
DOI: 10.1161/atvbaha.118.311252
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Protects Against Atherosclerosis in Male Mice by Targeting Thymic Epithelial Cells—Brief Report

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 39 publications
0
19
1
Order By: Relevance
“…The male-to-female ratio of mortality from vascular disease is approximately 3:1 worldwide 46 . Previous studies indicate that low level or absent testosterone is associated with an increase in CAD events [18][19][20]47,48 , and testosterone declines with obesity and age 47 . An increase in atherosclerotic plaque deposition was detected in XY mice lacking CYP17A1, and consequently lacking testosterone, suggesting a protective role for this hormone against atherosclerotic plaque formation.…”
Section: Discussionmentioning
confidence: 99%
“…The male-to-female ratio of mortality from vascular disease is approximately 3:1 worldwide 46 . Previous studies indicate that low level or absent testosterone is associated with an increase in CAD events [18][19][20]47,48 , and testosterone declines with obesity and age 47 . An increase in atherosclerotic plaque deposition was detected in XY mice lacking CYP17A1, and consequently lacking testosterone, suggesting a protective role for this hormone against atherosclerotic plaque formation.…”
Section: Discussionmentioning
confidence: 99%
“…G-ARKO and E-ARKO male mice were generated as previously described (17,20). T-ARKO and E-ARKO male mice were generated by breeding AR +/flox female mice with male pLCK-Cre + mice (Stock no.…”
Section: Methods Animalsmentioning
confidence: 99%
“…The incidence rates of hypertension and coronary artery disease have long been known to be higher in men than in women [18][19][20] , but only recently has evidence begun to accumulate indicating that low concentrations of androgens are associated with vascular injury. Notably, male patients receiving androgen deprivation therapy have an increased risk of cardiovascular disease 21 , while exogenous testosterone supplementation protects cardiac myocytes 22 . Experiments in male mice showed that testosterone protects against atherosclerosis by targeting thymic epithelial cells 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, male patients receiving androgen deprivation therapy have an increased risk of cardiovascular disease 21 , while exogenous testosterone supplementation protects cardiac myocytes 22 . Experiments in male mice showed that testosterone protects against atherosclerosis by targeting thymic epithelial cells 21 . In addition, androgens were shown to play an antihypertensive role in spontaneously hypertensive rats, while androgen de ciency could trigger the development of hypertension 23 .…”
Section: Discussionmentioning
confidence: 99%